Onboarding Models for Software Projects: An Ad-hoc Literature Review - Lima, Franciney O.; Bonifácio, Bruno A.; França, César (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2021: Anais do VI Workshop sobre Aspectos Sociais, Humanos e Econômicos de SoftwareDO - 10.5753/washes.2021.15889, 2021)
New hires usually should learn about the working process, organization structure, and company corporate culture and to be acquaintance with a very new environment. It requires company to organize throughout a well-planned onboarding process, but many companies are not aware of onboarding models and how to support onboard process to become more efficient. We aimed to characterize the main methods through an ad-hoc literature review. We provide practitioners and researchers with the rationale to identify onboarding models and characteristic of the main methods relate to onboarding Software Engineering.